Pengaruh Desain Produk, Kualitas Produk dan Kreativitas Iklan Terhadap Keputusan Pembelian Produk Aerostreet di Kota Batam - Elvan Maulana Rif’at; Hikmah Hikmah (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid growth of the local fashion industry, particularly footwear, demands companies like Aerostreet to enhance competitiveness through product innovation and effective marketing strategies. This paper analyzes how product design, product quality, and advertising creativity affect Aerostreet product purchase decisions in Batam City. Using a quantitative approach and data from 204 purposively selected consumers, the study applies multiple linear regression with SPSS 29. Results confirm that all three variables significantly influence consumer decisions, both independently and jointly. An adjusted R² score of 48.8% indicates strong explanatory power over consumer purchasing behavior. These findings suggest that a combination of attractive design, good quality, and creative advertising is crucial in encouraging consumers to purchase Aerostreet products